Sustainability of switch on-switch off (SOSO) mining: Human resource development tailored to technological solutions. (October 2021) - Moore, K.R.; Moradi, S.; Doyle, K.; Sydd, O.; Amaral, V.; Bodin, J.; Brito-Parada, P.R.; Dudley, F.; Fitzpatrick, R.; Foster, P.; Goettmann, F.; Roberts, D.; et al.
Abstract: Adaptable, mobile, modularised technical solutions were piloted for switch on-switch off (SOSO) mining at test sites in the west Balkans. Pre-training occurred at the site of module construction and on the mine site in order to transfer knowledge relating to the rapid deployment, commissioning and operation of mining and processing units, in a mature health and safety culture. Translation of extensive documentation, describing operation of the equipment, into local languages and visual aids supported communication. Consideration of the activities required to deploy and operate prototype solutions revealed how characteristics of a SOSO workforce differed from other types of mining. Deployment of modularised plant employed fewer workers than traditional stick-build of a processing plant, but selective mining and processing of complex and variable deposits limited the potential for automation and required operator control. A workforce with mixed levels of experience was most amenable to development of a mature health and safety culture. The total number of employees was small at an individual site and might remain small, even in a multi-deposit, regional business model. However, employment is higher per unit of production than for conventional large-scale mining. The duration of employment is shorter than for large-scale mining but employment can nevertheless be important where there are few alternative opportunities and where it can increase the skills-base to support a more diversified local economy. SOSO mining constitutes a new relationship between society and the mining industry, which needs further consideration for greater resilience in the local community and increased social sustainability. Highlights: Transformational change in the mining sector will include small-scale mining. Automation is limited by low CAPEX and a requirement for operator control. Switch on–switch off mining workforces are small, with mixed experience. Knowledge transfer approaches are designed for mature safety culture. Expansion of local skills base is a route from mining to economic diversification.